The Anxiety Levels of the Parents of Premature Infants and Related Factors - Raziye Çelen; Fatma Taş Arslan (Galenos Yayinevi, 2017)
Aim: The aim was to determine the anxiety levels of parents with premature infants and related factors. Materials and Methods: This comparative descriptive study was conducted in the neonatal intensive care unit of four hospitals located in Konya, Turkey between March and April 2012 with the parents (n=194; 97 mothers, 97 fathers) of premature infants who were 32-37 weeks gestational. Data were collected using Parents and Infant Information Form prepared by the researchers, and State-Trait Anxiety Inventory Scale. Results: The mean state anxiety scores of the mothers and fathers were similar (p>0.05). The mothers had higher mean trait anxiety scores compared to the fathers and this difference was found to be statistically significant (p<0.05). Conclusion: It was observed that parents with premature infants experienced mild anxiety.